Evidence of positive selection associated with placental loss in tiger sharks. Issue 1 (December 2016) - Swift, Dominic; Dunning, Luke; Igea, Javier; Brooks, Edward; Jones, Catherine; Noble, Leslie; Ciezarek, Adam; Humble, Emily; Savolainen, Vincent
Abstract Background All vertebrates initially feed their offspring using yolk reserves. In some live-bearing species these yolk reserves may be supplemented with extra nutrition via a placenta. Sharks belonging to the Carcharhinidae family are all live-bearing, and with the exception of the tiger shark (Galeocerdo cuvier ), develop placental connections after exhausting yolk reserves. Phylogenetic relationships suggest the lack of placenta in tiger sharks is due to secondary loss. This represents a dramatic shift in reproductive strategy, and is likely to have left a molecular footprint of positive selection within the genome. Results We sequenced the transcriptome of the tiger shark and eight other live-bearing shark species. From this data we constructed a time-calibrated phylogenetic tree estimating the tiger shark lineage diverged from the placental carcharhinids approximately 94 million years ago. Along the tiger shark lineage, we identified five genes exhibiting a signature of positive selection. Four of these genes have functions likely associated with brain development (YWHAE andARL6IP5 ) and sexual reproduction (VAMP4 andTCTEX1D2 ). Conclusions Our results indicate the loss of placenta in tiger sharks may be associated with subsequent adaptive changes in brain development and sperm production.